Low-cost Kerfless Wafers with Gradient Dopant Concentration Exceeding 19% Cell Efficiency in PERC Production Line. (August 2016) - Jonczyk, Ralf; Lorenz, Adam; Ersen, Ali; Hofstetter, Jasmin; Hübener, Kati; Duncker, Klaus; Scharf, Jessica; Neibergall, Larissa; Petter, Kai; Müller, Jörg; Jeong, Daniel
Abstract: Industry-leading multi-crystalline PERC processing has been applied to kerfless wafers made directly from molten silicon using Direct Wafer™ technology, avoiding the need for ingot production and sawing of bricks into wafers, thus providing significant cost saving potential. Efficiency averaged 18, 7% and a champion efficiency of 19, 1% was achieved on wafers with uniform doping using only mass production tools and processes. An additional efficiency gain was obtained using non-uniform doping, with a higher dopant concentration on the backside of the wafers that we call "drift field wafers". Simulations predict an efficiency increase of up to 0, 9% in efficiency. In the first test, we demonstrated increased efficiency by 0, 3% compared to uniformly doped wafers, leading to an average of 19, 0%, with single cells > 19, 3%. Further refinement of the wafer doping properties and co-optimization with mainstream cell process technologies will help accelerate the silicon PV learning curve and drive down costs for the prevailing multi-crystalline market.